Damage imaging in composite plate by using double-turn coil omnidirectional shear-horizontal wave magnetostrictive patch transducer array. (10th May 2017) - Liu, Zenghua; Zhong, Xuwen; Xie, Muwen; Liu, Xiucheng; He, Cunfu; Wu, Bin
Abstract : A double-turn coil omnidirectional shear-horizontal wave magnetostrictive patch transducer (DC-OSH-MPT) array for imaging detection in composite plates is presented. DC-OSH-MPT parameters are optimized in order to make the transducer more suitable for imaging detection. Besides, the characteristic of the lowest shear-horizontal mode (SH0 ), which can be generated and received in all directions by DC-OSH-MPT bonded on composite plate, is beneficial for imaging. Due to anisotropic property of composite plates, the group velocity of SH0 mode in different azimuthal directions was experimentally measured in damage imaging. The location of simulated damage, which was a bonded circular cylinder, was estimated by DC-OSH-MPT array and ellipse imaging algorithm. The imaging results have demonstrated that DC-OSH-MPT can be considered as a spatially distributed array suitable for imaging detection in composite plates.